Karl R. Popper’s anti-psychologism - Słomski, Wojciech (Folia Philosophica, 2001)
The author of the paper discusses Popper’s theory which he himself called “the theory of three worlds”. He tries to establish whether this conception can be treated as a tool of explanation of the essence of human cognition. In order to realise the task undertaken, the author assumes that this theory should not be treated either too strictly or too literally. He points out the difficulties resulting from a too consequent and too rigorous treatment of Popper’s theory. He simultaneously defines reasons for which Popper himself treated the conception of three worlds as a comfortable and useful metaphor rather than as a scientific theory. In his further considerations the author attempts to show the similarities and differences between Poppers theory of objective knowledge and I. Kant’s theory of perception as well as between Popper’s conception and A. Tarski’s theory of metalanguage. The author ends his article with showing some similarities between Popper’s theory and Freud's psychoanalysis.